An Analysis and Implementation of Local Area Network (LAN) As Data Communication Media In Computer-Based Test at SMPN 19 of Central Bengkulu - Herdiansyah Herdiansyah; Toibah Umi Kalsum; Rizka Rizka (Jurnal Komputer, Informasi dan Teknologi, 2021)
This study aims to build a LAN network infrastructure at SMPN 19 Bengkulu Tengah, implement a computer-based exam system using Moodle, optimize the use of computers at SMPN 19 Bengkulu Tengah, and implement a teaching and learning process by utilizing information technology. This research uses action research research methods. In the action research method, the researcher describes, interprets and explains a condition at the same time by conducting an intervention with the aim of improvement or participation. The results of this study indicate that the use of a computer-based test application on a LAN network that has been implemented at SMPN 19 Bengkulu is running well according to the results of service quality testing with a delay parameter of 6.47 ms, jitter of 1.64 ms, and packet loss of 0.998% and The server used in this study also has a fairly good performance which can be seen from the CPU usage by 20%, memory usage by 88%, and network usage of 1 kbps.